A-kinase anchor protein 4 (AKAP4) a promising therapeutic target of colorectal cancer. Issue 1 (December 2015) - Jagadish, Nirmala; Parashar, Deepak; Gupta, Namita; Agarwal, Sumit; Purohit, Sapna; Kumar, Vikash; Sharma, Aditi; Fatima, Rukhsar; Topno, Amos; Shaha, Chandrima; Suri, Anil
Abstract Background Colorectal cancer (CRC) ranks third among the estimated cancer cases and cancer related mortalities in the Western world. Early detection and efficient therapy of CRC remains a major health challenge. Therefore, there is a need to identify novel tumor markers for early diagnosis and treatment of CRC. Methods A-kinase anchor protein 4 (AKAP4) gene and protein expression was monitored by quantitative polymerase chain reaction (qPCR), reverse transcription (RT)-PCR and Western blotting in normal colon tissue lysate, normal colon epithelial cells and in colon cancer cell lines viz., Caco-2, COLO205, COLO320DM, HCT-15, HCT116, HT-29, SW480, and SW620. The effect of AKAP4 on cellular growth, migration and invasion abilities was studied using gene silencing approach. The role of AKAP4 in various pathways involved in cell cycle, apoptosis, senescence was investigated inin vitro and in human xenograft mouse model. Results Our studies showed that AKAP4 gene and protein expression was expressed in all colon cancer cells while no expression was detectable in normal colon cells. Ablation of AKAP4 led to reduced cellular growth, migration, invasion and increased apoptosis and senescence of CRC cells inin vitro assays and tumor growth in human xenograft mouse. Human colon xenograft studies showed a significant decrease in the levels of cyclins B1, D and E and cyclin dependent kinases such as CDK1, CDK2, CDK4 and CDK6. Interestingly, an up-regulation in the levels of p16 and p21 was also observed. Besides, an increase in the levels of pro-apoptotic molecules AIF, APAF1, BAD, BID, BAK, BAX, PARP1, NOXA, PUMA and cyt-C and Caspase 3, 7, 8 and 9 was also found in cancer cells as well as in xenograft tissue sections. However, anti-apoptotic molecules BCL2, Bcl-xL, cIAP2, XIAP, Axin2 and Survivin were down regulated in these samples. Our data also revealed elevated expression of epithelial marker E-cadherin and down regulation of EMT markers N-cadherin, P-cadherin, SLUG, α-SMA, SNAIL, TWIST and Vimentin. Further ablation of AKAP4 resulted in the down regulation of invasion molecules matrix metalloproteinase MMP2, MMP3 and MMP9. Conclusion AKAP4 appears to be a novel CRC-associated antigen with a potential for developing as a new clinical therapeutic target.